Pengaruh Likuiditas, Leverage, dan Kebijakan Dividen terhadap Konservatisme Akuntansi di Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Deby Arsita; Hestin Sri Widiawati; Faisol Faisol (BADAN PENERBIT STIEPARI PRESS, 2025)
This research is driven by the non-optimal implementation of accounting conservatism in Indonesia as indicated by various empirical findings related to financial statement engineering, specifically in the context of the insurance industry which faces high risk exposure and policy intervention. The purpose of this study is to examine the effect of liquidity, leverage, and dividend policy on accounting conservatism in insurance companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The approach in this study uses a quantitative approach with purpose sampling as a sample determination. Obtained 9 companies with a total of 45 observation data for 5 years. The data source in this study is secondary data derived from annual financial reports that can be accessed on the official IDX website. Data processing uses panel data regression analysis through a random effect model approach with STATA 17 software. This study shows the findings that liquidity has a significant effect on accounting conservatism, while leverage and dividend policy do not. Simultaneous testing, the three independent variables have a significant effect on accounting conservatism. This finding indicates that liquidity, leverage, and dividend policy, in financial reporting have a substantial influence on the practice of accounting conservatism because it is significant for managerial decisions and regulatory policies.